Clinical profile of dengue fever in children: analysis of 2017 outbreak from Central Kerala, India - K., Senthil Kumar; N. K., Rajendran; C., Ajith Brabhukumar (International Journal of Contemporary Pediatrics, 2018)
Background: In India, dengue epidemics are becoming more frequent (WHO, 2008). The majority of dengue viral infections are self-limiting, but complications may cause high morbidity and mortality. The objective of this study is to assess the clinical profile of the dengue infection in children less than 15 years of age and to evaluate the outcomes of dengue fever from March 2017 to July 2017 at the Pediatric Department of Karuna Medical College, the tertiary care hospital in Palakkad. Methods: In this retrospective study, medical records were reviewed and analyzed. Patients with suspected dengue infection were classified further into 2 groups, Dengue fever (probable dengue, dengue with warning signs) and ‘Severe Dengue’ (dengue hemorrhagic fever and/or dengue shock syndrome (DHF/DSS) according to WHO. Results: A total of 77 cases were classified into 67 (87%) non-severe and 10 (13%) severe dengue cases. The most common age of presentation was above 10 yrs. The mean age of admission was 8.9 yrs. The most common presenting symptom was fever seen in 93% followed by vomiting in 68%. Elevation in Aspartate transaminase (SGOT) and thrombocytopenia were found in 32.4 %. Conclusions: High grade fever, vomiting, abdominal pain and skin rash with normal or low platelet count were the presenting features. Early diagnosis, monitoring and prompt supportive management can reduce mortality.